2017
DOI: 10.2166/ws.2017.201
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of trihalomethanes in the air of two indoor swimming pool facilities using different type of chlorination and different types of water

Abstract: Certain aspects of the distribution of disinfection by-products (DBPs) in the air of indoor swimming pools, the exposure of the users, and possible health effects have not been well documented. To determine the distribution of trihalomethanes (THM), measurements were performed at 0.05 m, 0.60 m and 1.50 m above the water surface. These heights were chosen to measure the exposure in the breathing zone of the users. Air samples were collected from two indoor swimming pool facilities in Norway. Facility 1 uses ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
(22 reference statements)
2
6
0
Order By: Relevance
“…Although not specifically investigated, these unusually high TCM concentrations were likely due to the fact that these pools had recently been covered by pool blankets. Compared to the other investigated pools, higher concentrations (31 to 174 µg/m 3 ) of BDCM were also reported above these three pools at this facility, with only a few other studies reporting comparable concentrations (39 to 155 µg/m 3 ) . In the air above other chlorinated pools in this study, BDCM was measured at concentrations of 3.7 to 15 µg/m 3 , which are generally similar to those reported in most other studies, up to 26 µg/m 3 (as summarized by Carter and Joll).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Although not specifically investigated, these unusually high TCM concentrations were likely due to the fact that these pools had recently been covered by pool blankets. Compared to the other investigated pools, higher concentrations (31 to 174 µg/m 3 ) of BDCM were also reported above these three pools at this facility, with only a few other studies reporting comparable concentrations (39 to 155 µg/m 3 ) . In the air above other chlorinated pools in this study, BDCM was measured at concentrations of 3.7 to 15 µg/m 3 , which are generally similar to those reported in most other studies, up to 26 µg/m 3 (as summarized by Carter and Joll).…”
Section: Resultssupporting
confidence: 87%
“…While significantly higher concentrations (95 and 205 µg/m 3 ) have been previously reported,12,55 DBCM concentrations measured in this study are generally similar to most other reported studies 15,31,44,47,48,56,57. TBM was detected in the air above all chlorinated pools at concentrations of 3.4 to 36 µg/m 3 , which are similar to most other studies, as summarized by Carter and Joll, 1 although two studies53,54 have reported significantly higher TBM concentrations (103 and 319 µg/m 3 ) in the air above chlorinated pools, with another study reporting TBM at concentrations up to 1910 µg/m 3 above a brominated spa 52.…”
supporting
confidence: 92%
“…This is due to the air velocity impact on the pool evaporation rate. Since the space above the water surface is the occupant zone by definition, the traditional ventilation concept provides low ventilation efficiency and consequently relatively high values of DBP have been observed (Nitter et al, 2018). However, this design is in accordance with the present HVAC guidelines.…”
Section: Apply Better Disinfection Methodsmentioning
confidence: 71%
“…• Numerous disinfection by-products (Richardson et al, 2010;Weaver et al, 2009), • Occurrence and human consequences (Shaw, 1986;Benoit & Jackson, 1987;Kim et al, 2002;Righi et al, 2014;Lévesque et al, 2015;Zhang et al, 2015;Chowdhury, 2016;Nitter et al, 2018;Gabriel et al, 2019;Nitter & Svendsen, 2019a), • Formation of DBP (Jmaiff Blackstock et al, 2017;Kim et al, 2017;Fakour & Lo, 2018), • The impact of water treatment (Weng et al, 2012;Hansen et al, 2012;Weng et al, 2013;Spiliotopoulou et al, 2015;Nitter & Svendsen, 2019b), • Impact on the users and the user's uptake (Chu et al, 2013;Fernández-Luna et al, 2013;Font-Ribera et al, 2016;Hang et al, 2016;Parrat et al, 2012;Xiao et al, 2012).…”
Section: Indoor Air Qualitymentioning
confidence: 99%
See 1 more Smart Citation